Elevated Serum Leptin Levels in Patients With Eosinophilic Chronic Rhinosinusitis - Imoto, Yoshimasa; Ueki, Shigeharu; Kato, Yukinori; Yoshida, Kanako; Morikawa, Taiyo; Kimura, Yukihiro; Kidoguchi, Masanori; Tsutsumiuchi, Toshiki; Koyama, Keisuke; Adachi, Naoto; Ito, Yumi; Ogi, Kazuhiro; et al. (Frontiers in Pharmacology, 2022)
Background: Eosinophilic chronic sinusitis (ECRS) is a subtype of CRS with nasal polyps (CRSwNP) that is frequently comorbid with asthma. Notably, ECRS patients often show a high recurrence of NPs after surgical resection. Leptin is a hormone produced by adipocytes that has been implicated in airway inflammatory diseases. However, to date, the role of leptin in ECRS has not been investigated. Objective: To determine whether the serum levels of leptin are altered in patients with ECRS. Methods: In total, 40 patients with ECRS, 15 patients with non-eosinophilic CRS (non-ECRS), and 12 individuals without CRS (control) were included in this study. Patient’s serum leptin levels were assessed, and the number of eosinophils in their NPs were measured through a histological evaluation of the three densest areas with cellular infiltrate beneath the epithelial surface. Finally, nasal fibroblast cultures established from NPs were stimulated with varying concentrations of recombinant leptin in vitro to determine whether leptin affects eotaxin-3 (Chemokine (C-C motif) ligand 26 :26: CCL26) expression. Results: The serum leptin levels in both the ECRS and non-ECRS groups were significantly higher than those in the control subjects (P < 0.0001 vs. ECRS; P < 0.05 vs. non-ECRS). Furthermore, ECRS patients displayed significantly elevated serum leptin levels compared to non-ECRS patients (P < 0.001), although there was no difference in body mass index between the groups. Notably, serum leptin levels were correlated with the proportion of eosinophils in peripheral blood (r = 0.3575, P < 0.01) and the number of eosinophils in NPs (r = 0.5109, P < 0.0001). Serum leptin levels were also correlated with eotaxin-3 mRNA expression in NPs (r = 0.5374, P < 0.01). Finally, leptin significantly augmented eotaxin-3 expression in nasal fibroblasts established in vitro from NPs in a leptin receptor-dependent manner (P < 0.05). Conclusion: Leptin levels are elevated in ECRS patients and may both promote and indicate the severity of ECRS as well as systemic type 2-biased inflammatory responses. Combined, these data indicate that circulating leptin may play a significant role in the development of eosinophilic inflammation in NPs.